Mercury volatilisation and phytoextraction from base-metal mine tailings - Moreno, Fabio N.; Anderson, Chris W.N.; Stewart, Robert B.; Robinson, Brett H. (Environmental pollution (1987), 2005)
Experiments were carried out in plant growth chambers and in the field to investigate plant-mercury accumulation and volatilisation in the presence of thiosulphate (S 2O 3)-containing solutions. Brassica juncea (Indian mustard) plants grown in Hg-contaminated Tui mine tailings (New Zealand) were enclosed in gastight volatilisation chambers to investigate the effect of ammonium thiosulphate ([NH 4] 2S 2O 3) on the plant-Hg volatilisation process. Application of (NH 4) 2S 2O 3 to substrates increased up to 6 times the Hg concentration in shoots and roots of B. juncea relative to controls. Volatilisation rates were significantly higher in plants irrigated only with water (control) when compared to plants treated with (NH 4) 2S 2O 3. Volatilisation from barren pots (without plants) indicated that Hg in tailings is subject to biological and photochemical reactions. Addition of sodium thiosulphate (Na 2S 2O 3) at 5 g/kg of substrate to B. juncea plants grown at the Tui mine site confirmed the plant growth chambers studies showing the effectiveness of thio-solutions at enhancing shoot Hg concentrations. Mercury extraction from the field plots yielded a maximum value of 25 g/ha. Mass balance studies revealed that volatilisation is a dominant pathway for Hg removal from the Tui mine site. A preliminary assessment of the risks of volatilisation indicated that enhanced Hg emissions by plants would not harm the local population and the regional environment. Mass balance studies indicated that volatilisation was a dominant pathway for mercury removal.